Novel Anti-Acanthamoebic Activities of Irosustat and STX140 and Their Nanoformulations - Ruqaiyyah Siddiqui; Mutasem Rawas-Qalaji; Mohammed I. El-Gamal; Sreedevi Sajeev; Jayalakshmi Jagal; Seyed-Omar Zaraei; Rawan M. Sbenati; Hanan S. Anbar; Wolfgang Dohle; Barry V. L. Potter; Naveed Ahmed Khan (MDPI AG, 2023)
Pathogenic Acanthamoeba produce keratitis and fatal granulomatous amoebic encephalitis. Treatment remains problematic and often ineffective, suggesting the need for the discovery of novel compounds. For the first time, here we evaluated the effects of the anticancer drugs Irosustat and STX140 alone, as well as their nanoformulations, against A. castellanii via amoebicidal, excystment, cytopathogenicity, and cytotoxicity assays. Nanoformulations of the compounds were successfully synthesized with high encapsulation efficiency of 94% and 82% for Irosustat and STX140, respectively. Nanoparticles formed were spherical in shape and had a unimodal narrow particle size distribution, mean of 145 and 244 nm with a polydispersity index of 0.3, and surface charge of −14 and −15 mV, respectively. Irosustat and STX140 exhibited a biphasic release profile with almost 100% drug released after 48 h. Notably, Irosustat significantly inhibited A. castellanii viability and amoebae-mediated cytopathogenicity and inhibited the phenotypic transformation of amoebae cysts into the trophozoite form, however their nanoformulations depicted limited effects against amoebae but exhibited minimal cytotoxicity when tested against human cells using lactate dehydrogenase release assays. Accordingly, both compounds have potential for further studies, with the hope of discovering novel anti-Acanthamoeba compounds, and potentially developing targeted therapy against infections of the central nervous system.